Iyatayet, [NOB-002] vertebrate fauna dataset ... - Darwent, Christyann; Darwent, John; Eldridge, Kelly Anne; Rasic, Jeffrey T.; Tremayne, Andrew Hale (Neotoma Paleoecology Database, 2025)
Raw data for the Iyatayet, [NOB-002] vertebrate fauna dataset submitted to the Neotoma Paleoecology Database. Data is available through the landing page in JSON format. The landing page referenced by the DOI also contains links to publications and a map-based viewer for the dataset. The Neotoma Paleoecology Database maintains a homepage at https://www.neotomadb.org. ...